Analysis of the Effect of Rational Emotional Intervention Combined with Hierarchical Management Mode on Improving the Psychological Stress of Emergency Nurses and Trainee Nurses - Shirui Liu; Xiangsu Li; Xianghong Yin; Liqun Wang (Emergency Medicine International)
Purpose. To explore the effect of rational emotional intervention combined with hierarchical management mode on improving the psychological stress of emergency nurses and trainee nurses. Methods. 50 emergency nurses who worked or practiced in our hospital from June 2019 to May 2021 were selected as the research object. From June 2019 to May 2020, our hospital adopted the traditional management mode. From June 2020 to May 2021, our hospital adopted the rational emotional intervention combined with hierarchical management mode. The psychological state, work stress, stress response, job burnout, and sleep quality of emergency nurses were compared before and after intervention. Results. Compared with before intervention, the scores of self-rating anxiety scale and self-rating depression scale, the work stress scores, the Maslach burnout inventory score, the Pittsburgh sleep quality index score of emergency nurses decreased after intervention (P<0.05). Compared with before intervention, the stress coping scores of emergency nurses increased after intervention (P<0.05). Conclusion. The rational emotional intervention combined with hierarchical management mode can improve the psychological pressure of emergency nurses and trainee nurses, reduce job burnout, improve stress coping ability, and improve sleep quality.